EXPERIMENTAL STUDIES OF A STEEL FRAME MODEL WITH AND WITHOUT BUCKLING-RESTRAINED BRACES - Guerrero Bobadilla, Héctor; Ji, Tianjian; Escobar, José Alberto (Revista Ingeniería Sísmica, 2016)
This paper presents comparative experimental studies of a five-storey steel-frame model at a scale of 1/10 with, and without, buckling-restrained braces (BRBs). The building model was subjected to free vibration tests and shaking table tests. The latter were conducted using low-intensity white noise and seismic input. From the free vibration tests and shaking table tests with low-intensity white noise, it was found that the BRBs contributed a significant amount of damping. This happened to the model even at low levels of vibration. The shaking table tests with seismic input were conducted using seven earthquake records, taken in the lakebed zone of Mexico City with seismic intensities from pga=0.1g to 0.25g. At an intensity of pga=0.1g, the results show that the model fitted with BRBs had a significantly smaller response than the bare model, in terms of displacement, inter-storey drift, floor velocity and floor acceleration. The higher intensities were only applied to the model fitted with BRBs. The results indicate that the model with BRBs was able to withstand about 2.5 times the seismic intensity of the bare model, in terms of lateral displacement, inter-storey drift and Arias Intensity, as a measure of the energy contents of the movement. At the end of the tests, all BRBs were removed and the model remained in its original undamaged state.